Social-psychological Aspects of Bullying: Interconnection of Aggressiveness and School Anxiety - Tarasova S.Ju.; Osnitsky A.K.,; Enikolopov S. N., (Психологическая наука и образование (2007. Online), 2017)
Bullying is seen as a variant of aggression. Natural interconnections between contents of teenagers’ fears, anxiety and aggression are analyzed. The longitudinal research results are presented, in the framework of which four consecutive measures of anxiety and the following aggressiveness indexes of 70 6th form pupils, and then 7th form ones are compared. It is being clarified, to what extent aggressive behavior risk is related to animosity as a negative notional attitude of an individual. Hostility stably and positively correlates with school, self-esteem, interpersonal and mystical anxiety among teenagers. Social situation of uncertainty, connected to constant transformation of social norms, exerts heavy influence. According to research results, greatly isolated schoolchildren stand out in each class. It is them, who, according to the expert teachers assessment and included to observational results, are victims to aggressors as well as to “onlookers”, who take positions of passive aggressors. Victims are stably overly anxious, possess high level of hostility and are inclined to protective aggression in behavior. Their further transformation into aggressors can be safely assumed. This work was supported by grant RFH № 15-06-00052.